Penentuan Kadar Fenolik Total Ekstrak Etanol Tanaman Betadin (Jatropha multifida L.) Secara Spektrofotometri - Mia Arifka; Zulfisa Zulfisa (Journal Pharma Saintika, 2023)
The Betadine plant (Jatropha multifida L.) is one of the Indonesian medicinal plants which is empirically widely used to treat various types of infections. The Betadine plant (Jatropha multifida L.) is known to contain phenolic compounds which have antioxidant activity and have bactericidal, antiseptic and anthelmintic properties. In this study, the total phenolic content of the ethanol extract of the Betadin plant (Jatropha multifida L.) was determined spectrophotometrically using the Folin Ciocalteu method. Gallic acid was used as a standard comparison solution in this study. From the absorbance measurement results, a linear regression equation Ŷ = 0.624 + 0.001x was obtained with a coefficient of determination (R2) of 0.996. The total phenolic content in Betadin plants is 0.80115% w/w which is calculated as gallic acid